2017
DOI: 10.1039/c7ra03867d
|View full text |Cite
|
Sign up to set email alerts
|

Highly effective K-Merlinoite adsorbent for removal of Cs+ and Sr2+ in aqueous solution

Abstract: Cs+ and Sr2+ removal using K-MER adsorbent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…In Figure 1, 0.75 M KOH shows the most significant peaks at 20.8°, 28.8°, 34.2° and 42.4°. These observations are also supported by findings from Kakutani et al (2017) [13] after the hydrothermal reaction of silica powder with 4 M KOH and aluminium nitrate for 336 h. Compared with the values in the literature [11,14,15], the present study uses much lower KOH concentrations, which reduces production costs as well as helps to conserve the environment. It is suggested that 0.75 M of KOH is optimal for the transformation of kaolin into kalsilite.…”
Section: Effect Of Koh Concentrationsupporting
confidence: 87%
“…In Figure 1, 0.75 M KOH shows the most significant peaks at 20.8°, 28.8°, 34.2° and 42.4°. These observations are also supported by findings from Kakutani et al (2017) [13] after the hydrothermal reaction of silica powder with 4 M KOH and aluminium nitrate for 336 h. Compared with the values in the literature [11,14,15], the present study uses much lower KOH concentrations, which reduces production costs as well as helps to conserve the environment. It is suggested that 0.75 M of KOH is optimal for the transformation of kaolin into kalsilite.…”
Section: Effect Of Koh Concentrationsupporting
confidence: 87%
“…The argument is consistent with the findings of [13] after the researchers used a KOH concentration higher than 4.3 M when synthesising kalsilite using microcline as a precursor under hydrothermal conditions. Analogous results are also achieved by [14] when they used 4 M KOH added with an SiO 2 powder and Al(NO 3 ) 3 to obtain KAlSiO 4 after 336 hours using the hydrothermal reaction method. Compared with the above literature sources, this study shows metakaolinite can also be used as a precursor for the kalsilite synthesis under the hydrothermal reaction since it contains a high Si and Al composition with the Si:Al ratio close to 1.…”
Section: Resultssupporting
confidence: 57%
“…In addition, M-GO depicted higher adsorption capacity for Cs + than for Sr 2+ under the same experimental conditions. This can be attributed to the smaller hydrated ionic radius of Cs + [25] .…”
Section: Ph Effectmentioning
confidence: 99%